Workplace Violence Against Prehospital Paramedic Personnel (City and Road) and Factors Related to This Type of Violence in Iran - Sheikhbardsiri, Hojjat (Journal of interpersonal violence, 2022)
Medical personnel such as those working in emergency medical systems are in direct contact with the patient or the injured and are exposed to workplace violence. This study aimed to determine workplace violence against prehospital paramedical personnel and factors related to this type of violence in Iran. The cross-sectional study was conducted in 72 prehospital emergency centers affiliated with Kerman University of Medical Sciences in 2019. Using a researcher-made questionnaire, we assessed workplace violence and factors associated with this type of violence in prehospital paramedical personnel with a census method (N = 308). Data were analyzed using descriptive statistics including mean and standard deviation (SD), frequency, percentage, and analytic statistics, such as the Kolmogorov?Smirnov, ANOVA, t test, and multiple linear regression tests. The results of this study showed that the most frequent types of workplace violence were verbal violence (47%), physical violence (32.50%), cultural violence (16%), and no violence (4.50%), respectively. From the perspective of paramedical personnel, the total mean score of workplace violence was at a moderate level (52.19 ± 10.72). The most important factors affecting workplace violence from the perspective of paramedical personnel were ?lack of awareness of people about the duties of emergency medical personnel? and ?lack of specialists in prehospital (city or road) bases.? Majority of the paramedical personnel believed that ?no reaction and observance of patients and their families? rights? were the most important types of reactions. They also believed that violence was normal at the workplace and should not be considered in emergency medical services. Results suggest that national and local policies in Iran should provide prehospital paramedical personnel with various training courses about how to decrease the rate of workplace violence, promote public health, and decrease their psychological stresses and occupational burnout.